Gastrointestinal cell proliferation and crypt fission are separate but complementary means of increasing tissue mass following infusion of epidermal growth factor in rats. Issue 6 (1st June 2001) - Berlanga-Acosta, J; Playford, R J; Mandir, N; Goodlad, R A
Abstract : BACKGROUND AND AIMS: Epidermal growth factor (EGF) is a potent mitogen for the gastrointestinal tract and also influences the number of new crypts formed by crypt fission. The time course of these events and possible linkage between these two complementary mechanisms is however poorly understood. We therefore examined the temporal relationship of proliferation and fission in rats treated with EGF. METHODS: Osmotic minipumps were implanted subcutaneously into male Wistar rats to infuse EGF continuously (60 μg/rat/day) for periods of 1–14 days. Proliferation and crypt branching were quantified following vincristine induced metaphase arrest and morphometric assessment of microdissected tissue. RESULTS: In the small intestine, EGF significantly increased epithelial cell proliferation and crypt and villus area after 24 hours of EGF, although maximal effects were only reached following six days of infusion. EGF also resulted in an approximate 30% reduction in crypt fission in the small bowel. In the colon, EGF caused a twofold increase in epithelial cell proliferation one day after infusion, from 15.3 (2.3) to 29.6 (3.5) metaphases per crypt (p<0.01). Maximal effects were seen in rats receiving EGF for seven days. For all time points, colonic crypt size increased in response to EGF. The amount of branching increased following one day of infusion with EGF (from 15.3 (1.9) to 32.4 (5.5)%; p<0.001) but was significantly lower (approximately 25% of control values) following longer periods of infusion. Crypt fission did not correlate with crypt area. CONCLUSION: EGF has profound effects on cell proliferation and also altered crypt fission, with its actions on crypt fission most pronounced in the colon where it first increased and then decreased fission. EGF can thus be a potent stimulus for crypt fission during short term infusion and may reduce the number of branched crypts present in a resting or quiescent stage. Growth factors can alter cell mass by two separate but linked mechanisms, namely altered cell production and crypt fission.